Islamic Republic of Afghanistan : 2015 Article IV Consultation and First Review Under the Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Direct for the Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Afghanistan remains a poor fragile state that is far from self-reliance. Significant fiscal and banking vulnerabilities emerged in 2014. Domestic revenue collection fell below its 2013 level because of lower growth, declining imports, and lower compliance, while operating expenditure increased. The treasury cash balance fell to dangerously low levels in the second half of 2014, and domestic payment arrears and unfunded allotments emerged. The future path of the economy is highly dependent on the authorities' delivering on their economic reform commitments, continued donor support, and improvements in security.